An Unexpected Potassium Iodide‐Promoted Nucleophilic Substitution Reaction between 2‐Acyloxy‐2H‐azirines and Carboxylic Acids. Issue 20 (21st September 2016) - Duan, Xiyan; Yang, Kun; Liu, Jianwei; Kong, Xianglei; Liang, Ju; Zhou, Dongju; Zhou, Huiyun; Zhang, Yanping; Liu, Ning; Feng, Shuxiao; Gu, Guangna; Lu, Jun; et al.
Abstract: The acyloxy group of 2‐acyloxy‐2 H ‐azirines has been displaced by carboxylic acids to generate the corresponding 2‐acyloxy‐2 H ‐azirines by using potassium iodide as a promotor. This metal‐free method can be performed with a wide scope of substrates readily generating products in moderate to high yields. It also represents an example of nucleophilic substitution between esters and carboxylic acids under metal‐free reaction conditions for the first time. Abstract :